Maladministration In Land Acquisition Of Public Interest (Case Study: Solo-Yogyakarta Highway Project) - Sudjito Sudjito (Jurnal Dinamika Hukum, 2023)
This study aims to analyze the maladministration of land acquisition for the public interest (Case study: Solo-Yogyakarta Toll Road). This type of research is juridical-normative. The nature of the research: descriptive-qualitative, meaning that it provides an overview of the problem/object being studied. The data studied were limited to secondary data. Sources of data: documents, archives, previous research results, and other validated sources. Data analysis was carried out through the following stages: data reduction, data display, data processing, and data meaning. Conclusions are drawn inductively. The results of the study show: (1). It is true that there has been maladministration in land acquisition. The committee has carried out deceitful practice, namely the practice of lying or being dishonest to the public regarding the contents of the regulation, as well as the assessment of compensation; (2). In the practice of providing compensation for non-physical components, it is not discussed, and is not taken into account, so that the amount of compensation is low; (3). The former holders of land rights feel very disadvantaged because non-physical compensation which includes: moving costs, solatium, PPAT fees, BPHTB fees, and waiting interest expenses, are not taken into account. In fact, these costs are the rights of the people affected by the land acquisition. In order to buy replacement land or move, they had to pay for it themselves.Keywords: Maladministration, compensation, land acquisition